2008
DOI: 10.1016/j.cpr.2008.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Addressing mental health disparities through clinical competence not just cultural competence: The need for assessment of sociocultural issues in the delivery of evidence-based psychosocial rehabilitation services

Abstract: Recognition of ethnic/racial disparities in mental health services has not directly resulted in the development of culturally responsive psychosocial interventions. There remains a fundamental need for assessment of sociocultural issues that have been linked with the expectations, needs, and goals of culturally diverse consumers with severe and persistent mental illness. The authors posit that embedding the assessment of sociocultural issues into psychosocial rehabilitation practice is one step in designing cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 117 publications
0
49
0
1
Order By: Relevance
“…The relevance of cultural factors to both diagnosis and treatment suggests potential benefits of identifying personal and cultural factors and integrating that understanding into the provision of care, including psychoeducation and other interventions to address culturally related stigma and shame. Such an approach has been recommended by experts (Mezzich et al 2009;Yamada and Brekke 2008) and organizations, including the APA (DSM-5 Cultural Formulation Interview; American Psychiatric Association 2013a), The Joint Commission (2010,2011), and the Office of Minority Health of the U.S. Department of Health and Human Services (2014).…”
Section: Rationalementioning
confidence: 99%
“…The relevance of cultural factors to both diagnosis and treatment suggests potential benefits of identifying personal and cultural factors and integrating that understanding into the provision of care, including psychoeducation and other interventions to address culturally related stigma and shame. Such an approach has been recommended by experts (Mezzich et al 2009;Yamada and Brekke 2008) and organizations, including the APA (DSM-5 Cultural Formulation Interview; American Psychiatric Association 2013a), The Joint Commission (2010,2011), and the Office of Minority Health of the U.S. Department of Health and Human Services (2014).…”
Section: Rationalementioning
confidence: 99%
“…A clear guideline for a Cultural Formulation (CF) is presented in the DSM-IV-TR (APA, 2000). The CF, however, has challenges in its implementation (Rohlof, Knipscheer, & Kleber, 2009;Smart & Smart, 1997;Yamada & Brekke, 2008).…”
Section: Challenges Associated With Multiple Cultural and Religioumentioning
confidence: 99%
“…The distance between the client's identity (primary cultural identity, values, philosophical assumptions, and culture of origin) and host culture will determine how the client will approach life, and the formation of a postmigration identity in the host culture. Addressing sociocultural factors in understanding the client's concerns, specific to privilege, oppression, and disparities in services is essential (Ibrahim, 2010;Yamada & Brekke, 2008).…”
Section: Cultural Assessmentmentioning
confidence: 99%
“…16 Research has also demonstrated the significance to developing competence in the context of the various socio-cultural issues that need to be embedded into PSR programmes in order to ensure their effectiveness. 17 This is especially relevant in multicultural South Africa.…”
Section: Introductionmentioning
confidence: 99%